Spot the trachea! A wide paratracheal air cyst of not easy definition - Crisafulli, Ernesto; Lazzari, Chiara; Longo, Chiara; Bernardinello, Nicol; Alfieri, Veronica; Chetta, Alfredo (Acta Biomedica Atenei Parmensis, 2018)
We report a case of a 68-year-old woman with an occasional image of a wide paratracheal oval air cyst of not easy definition. Patient had never received a chest X-ray and she had never suffered from symptoms that needed to investigate the trachea or the neck. The diagnostic hypothesis was a wide tracheal diverticulum or a bronchogenic cyst.